Understanding the Cryptosporidium species and their challenges to animal health and livestock species for informed development of new, specific treatment strategies - Rideout, Hannah; Cook, Alasdair J. C.; Whetton, Anthony D. (Frontiers in Parasitology, 2024)
Cryptosporidium species are parasitic organisms of vertebrates with a worldwide distribution. They have an important impact globally upon human and animal health, and livestock productivity. The life cycle of these species is complex and difficult to disrupt to improve human health, animal health, food security and economic growth. This may contribute to the fact that no new treatment strategy has been widely accepted or applied in livestock for years. Here we consider the natural history of these parasites, their biochemistry and economic impact. Using recent developments in understanding these parasites we then consider viable and affordable approaches to enhancing control of their effects on livestock. These are based on advances in drug discovery, omics research and artificial intelligence applications to human and veterinary medicine that indicate putative new therapeutic approaches.Cryptosporidium are protozoan pathogens that result in the enteric disease cryptosporidiosis (Helmy, Y. and Hafez, 2022). Previously they were classified as coccidia and considered to be intracellular parasites. However, recent research states they are members of a new class named cryptogregaria. In evolutionary terms this lies between coccidia and gregarine (Cavalier-Smith, 2014). Features that set them apart from coccidia include intracellular and extra-cytoplasmic localisation, feeder organ formation, presence of morphological oocysts, smaller oocysts, absence of sporocysts or micropyles, and, importantly, resistance to all available anti-coccidial drugs (Hijjawi et al., 2002)(Smith and Corcoran, 2004)(Helmy, Y. and Hafez, 2022). The re-classification has not been challenged since its publication meaning Cryptosporidium is now officially gregarine (Ryan et al., 2016). Gregarines are single-celled apicomplexan parasites that primarily infect the intestines of invertebrates and lower vertebrates (Leander,